Twardowski – Rubczyński – Hempel. Religia jako humanistyczny element myślenia o rzeczywistości społecznej - Kojkoł, Jerzy (Człowiek i Społeczeństwo, 2015)
This article offers an interpretation of the views of three thinkers who represent theoretical approaches to the social functions of religion. These are: K. Twardowski, W. Rubczyński i J. H. Hempel. The discussed views, which are characteristic of Polish philosophy, emphasize the import_ance or religion and all kinds of faith for shaping a human being who is open to “Others” and shaping spirituality based on altruism. The authors presented in the article have the highest respect for outstanding people who do not abandon themselves to passions, focus on the matters most import_ant for the state, promote sound patriotism and reject political nationalism.